The effect of solvent type and concentration on extraction of phenolic compounds and evaluation of antioxidant activity of Crataegus elbursensis L. leaf collected from Golestan province - Mohammad Moghaddam; Leila Mehdizade (فیزیولوژی محیطی گیاهی, 2022)
In order to investigate the effect of the type and concentration of solvent on the amount of extraction of phenolic compounds and antioxidant activity of Crataegus elbursensis leaves, a research was performed in two separate experiments. At first experiment the effect of solvent type (acetone, ethanol, methanol) at three concentrations (50, 80 and 100%) on extracted total phenolics content of C. elbursensis leaf was evaluated. At second experiment antioxidant capacity of produced extract from the best solvent at first experiment with the highest phenolic compounds (methanol 80%) was investigated by two different methods including total antioxidant and Fe reduction capacity. The results of these experiments showed that all three solvents; acetone, ethanol and methanol; in the form of mixture with water have more potential for extracting phenolic compounds toward the pure ones. The highest total phenolic content (118 mg GAE/g DW) was obtained at 80% concentration of all solvents, especially at methanol 80%. The results of evaluating antioxidant activity showed that with increasing the concentration of extract up to 500 µg/mL, antioxidant activity (0.8 mg/mL) was increased. Investigation of Fe reduction capacity indicated that with increasing the concentration of extract up to 800 µg/mL, the amount of absorption of the solvents contain the extract significantly increased. Therefore, according to the results of this study, the leaves of this plant can be used as the source of phenolics and antioxidants in different industries.